3D meso-scale fracture modelling of concrete with random aggregates using a phase-field regularized cohesive zone model. (1st December 2022) - Li, Hui; Huang, Yujie; Yang, Zhenjun; Yu, Kelai; Li, Q.M.
Abstract: This study develops a mesoscale fracture modelling method combining the phase-field regularized cohesive zone model (PF-CZM) and random aggregate models for simulating complicated 3D meso-scale damage and fracture in concrete-like quasi-brittle materials. In this method, the aggregates in the mortar are built using a random generating and packing algorithm, and their surrounding mortar-aggregate interfaces are obtained from an aggregate scaling algorithm. The PF-CZM with cohesive softening laws and an intrinsic length scale is used to model multi-crack initiation and propagation in the mortar and interfaces without remeshing. The method was first validated by a concrete cube under uniaxial tension, with the effects of the mesh size, the length scale, the tensile strength, and the fracture energy investigated in detail. Three concrete beam examples, one under mode-I fracture and two under mixed-mode fracture, were then modelled for further validation and demonstration for practical uses. It is found that the method can effectively simulate 3D stochastic fracture processes and accurately calculate load-carrying capacities with little mesh-dependence.